ATIM-24. TARGETING MYELOID DERIVED SUPPRESSOR CELLS: PHASE 0/1 TRIAL OF LOW DOSE CAPECITABINE + BEVACIZUMAB IN PATIENTS WITH RECURRENT GLIOBLASTOMA - Peereboom, David M (Neuro Oncol, 2017)
BACKGROUND: Glioblastoma creates an immunosuppressive environment that allows tumor growth. Myeloid derived suppressor cells (MDSCs), a class of immunosuppressive cells, mediate immunosuppression in GBMs. MDSCs are up-regulated in the blood of GBM patients. We have developed a novel strategy to target GBM immunosuppression using low dose 5-fluorouracil (5-FU) to target MDSCs. Marked MDSC depletion occurs at 5-FU doses in mice equivalent to <10% of the normal human dosing. Goal: proof of concept that MDSC suppression is feasible in GBM patients with low-dose capecitabine, an oral analogue of 5-FU. METHODS: Eligibility: Recurrent GBM in need of surgical resection; no prior capecitabine or bevacizumab. Cohorts of 3–6 patients receive low-dose capecitabine 150 mg/m2/d (dose level [DL] 1) for 7 days pre-surgery. Post-op, patients resume capecitabine for one cycle after which bevacizumab is added. Concentrations of blood MDSCs, immune cell, and relevant secreted factors are measured at baseline; pre- and post-op; and after the addition of bevacizumab. Tumors are assayed for MDSCs and glioma stem-like cells (GSCs). Primary endpoint: MDSC and T-Regulatory cell reduction after capecitabine. Secondary endpoints: Tumor concentrations of MDSCs, GSCs, and regulatory T-cells (T-regs); safety; and PFS6. RESULTS: Six patients have enrolled to date; data are available on 4. On DL1, MDSC reductions (range 12–28%) from baseline have not yet reached goal of 90%. T-regs fell slightly (range 0–12%). Cytotoxic T-cell (CTL) concentrations rose significantly (5, 28, 86, and 93%). No patient experienced grade 3 or higher toxicity. Two treatment-related SAEs (hemorrhage, non-neutropenic fever) have occurred. CONCLUSIONS: In the initial cohort, low dose capecitabine was associated with a modest reduction in MDSCs and a significant increase in CTLs. Toxicity has been minimal. One of 3 evaluable patients has reached 6 months free of progression. Dose escalation continues. (NCT02669173) (Supported by Musella Foundation, Blast GBM, Sontag Foundation, Velosano, Mylan Pharmaceuticals)